THE INFLUENCE OF MARKETING MIX ON CUSTOMER LOYALTY TOWARDS MUDHARABAH SAVINGS OF SHARIA COMMERCIAL BANK IN INDONESIA - Pasaribu, Fajar; Pasaribu, Mhd Hasan (Proceeding International Seminar of Islamic Studies, 2024)
This study aims to empirically prove the influence of marketing mix seen from product, price, place, promotion on customer loyalty at Bank Syariah Indonesia Medan Branch. The sampling technique uses purposive sampling totaling 150 people. Furthermore, the data collection technique used is a questionnaire. While the data analysis technique uses multiple linear regression. The results of this study show that the marketing mix seen from product and place has a significant influence on customer loyalty while price and promotion do not have a significant effect on customer loyalty.